Numerically investigation of MHD liquid lithium flow under cooling conditions in a circular channel - Erdem, Murat; Firat, Mujdat; Varol, Yasin (Pamukkale Univ, 2018)
In this study, the lithium fluid was numerically analyzed in a three-dimensional circular channel exposed to external magnetic field induction. The magnetic field is applied perpendicular to the flow direction of the channel. Re=2250 and the magnetic field strength was selected as 0T, 0.04T, 0.08T and 0.12T, respectively. Besides, while the fluid temperature is 473.15 K, the wall temperature is 373.15 K. Calculations were performed with ANSYS-Fluent commercial software. The effect of the magnetic field on the fluid velocity, pressure and temperature has presented graphically. While the magnetic field seriously has reduced the fluid velocity, the pressure has observed to increase. Also, it has been observed that the magnetic field affects the temperature differently in different regions of the channel along the pipe length.
Keywords: MHD; Magneto-hydrodynamics; Forced convection; Liquid lithium cooling; Computational fluid dynamic (CFD)